Bronchoscopic performance of bronchoalveolar lavage in Germany – a call for standardization: A request for BAL standardization - Hetzel, Juergen; Kreuter, Michael; Kähler, Christian; Kabitz, Hans-Joachim; Gschwendtner, Andreas; Eberhardt, Ralf; Costabel, Ulrich; Darwiche, Kaid (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
Background: Bronchoalveolar lavage (BAL) is a widely used clinical tool in diagnosing interstitial lung diseases. Although there are recommendations and guidelines, the procedure is not completely standardized. Varying approaches likely influence the conclusiveness of BAL data and may be one reason for the divergent judgement of their value between different centers. Objectives: To evaluate how BAL is performed in Germany using an electronically based survey. Methods: We conducted a cross-sectional online survey among all members of the German Respiratory Society. Results: 608 members responded to the survey and of these 500 perform lavages.  Most bronchoscopists (344/500) do not use a tube and have no anesthesiologist present during the procedure (405/500). Propofol is used by 76.8% and midazolam by 67.9% (n = 405), often in combination. A major difference was noted regarding the total volume of instillation. Many respondents use a predefined fixed amount of instilled volume (202/500), whereas an almost equal number use variable volumes based on the recovery (196/500). The minimum recovery volume predefined by 217/499 ranged from 3-150 ml (median 30 ml; mean 42.2 ± 55.1 ml). Most respondents did not transport their samples in special medium (61.5%) or on ice (72.8%). The average time between recovery and arrival at the lab was 115.6±267.0 min (n = 323). Conclusions: This study shows the broad spectrum of variations in the performance of BAL in Germany, which could have a negative effect on the method’s clinical value. There is a need for training and standardization of BAL performance.